Structure-Conduct-Performance Analysis of Skipjack Fish Industry in Banda Aceh City - Fitriansyah Pohan; Safrida Safrida; Anwar Deli (International Journal Labs, 2023)
The purpose of this study is to describe the structure conduct performance in the skipjack fish industry in Banda Aceh City, Analyze the influence of structure conduct performance in the skipjack fish industry in Banda Aceh city, and analyze the factors that affect the performance of the skipjack fish industry in Banda Aceh city. The number of samples is 4 companies that manage Skipjack Fish in Banda Aceh City. The market structure of the skipjack fish industry in Banda Aceh is oligopoly as seen from the value of market concentration and barriers to entry from 2011 to 2020. During this time span, the structure of the skipjack fish industry also showed market concentration and barriers to entry that were getting lower in value from year to year. This shows that competition in the skipjack fish industry is increasing. The skipjack fish industry in Banda Aceh sets a price strategy by following price rules made by outside parties such as the United States importing countries, for product strategies are carried out by classifying products based on the size and type of product treatment such as fresh skipjack fish and frozen skipjack fish. In the performance dimension, it was found that the average value of PCM for the 2011-2020 period was 33.88 percent with the largest PCM value occurring in 2018 at 44.33 percent and the lowest PCM in 2014 at 19.07 percent. Meanwhile, the average value on x-eff for the 2011-2020 period was 102.93 percent. The largest amount of internal efficiency occurred in 2019 at 147.99 percent, and the smallest x-eff value occurred in 2017 at 71.42 percent. The independent variables that are considered to affect the dependent variable (PCM) are CR4, MES, X-eff, PROD, and JLP. However, only x-eff and PROD have a significant effect on PCM. The rest such as CR4, MES, and JLP have an intangible effect because the value is greater than the real level of 0.05.